2021
DOI: 10.1111/bjh.17311
|View full text |Cite
|
Sign up to set email alerts
|

Non‐myeloablative human leukocyte antigen‐matched related donor transplantation in sickle cell disease: outcomes from three independent centres

Abstract: Summary Non‐myeloablative haematopoietic progenitor cell transplantation (HPCT) from matched related donors (MRD) has been increasingly utilized in sickle cell disease (SCD). A total of 122 patients received 300 cGy of total body irradiation (TBI), alemtuzumab, unmanipulated filgrastim‐mobilized peripheral blood HPC and sirolimus. The median follow‐up was four years; median age at HPCT was 29 years. Median neutrophil and platelet engraftment occurred on day 22 and 19 respectively; 41 patients required no plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 40 publications
1
59
2
Order By: Relevance
“…Many nonmyeloablative and reduced-intensity conditioning (RIC) HSCT regimens for SCD utilize alemtuzumab, a monoclonal antibody that targets the cell surface antigen CD52 found on lymphocytes. [11][12][13][14][15] The pharmacokinetics (PK) and pharmacodynamics (PD) of alemtuzumab have been examined, but primarily in patients with malignant conditions. [16][17][18] In a population PK/PD model created based on the data from patients with chronic lymphocytic leukemia (CLL), alemtuzumab appears to have a non-linear, time-dependent clearance that is affected by the white blood cell count (WBC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many nonmyeloablative and reduced-intensity conditioning (RIC) HSCT regimens for SCD utilize alemtuzumab, a monoclonal antibody that targets the cell surface antigen CD52 found on lymphocytes. [11][12][13][14][15] The pharmacokinetics (PK) and pharmacodynamics (PD) of alemtuzumab have been examined, but primarily in patients with malignant conditions. [16][17][18] In a population PK/PD model created based on the data from patients with chronic lymphocytic leukemia (CLL), alemtuzumab appears to have a non-linear, time-dependent clearance that is affected by the white blood cell count (WBC).…”
Section: Introductionmentioning
confidence: 99%
“…19 In contrast, our HSCT regimens for SCD used gradually increasing doses of alemtuzumab from 0.03 to 0.3 mg/kg/day, totaling 1.03 mg/kg over a 5-day period starting 7 days prior to the hematopoietic stem cell infusion. 11,12 Other HSCT regimens for nonmalignant disorders administered alemtuzumab more distal from the hematopoietic stem cell infusion date, from 22 days pre-HSCT to 19 days pre-HSCT, totaling 33 mg or 48 mg. 20 Because of these varying HSCT regimens, alemtuzumab clearance or the resulting systemic exposure were hypothesized to be a contributing factor to HSCT outcomes. In HSCT, the important elements that determine the overall success of the transplant conditioning regimen are the rates of graft rejection and toxicities from the regimen, such as graft-versus-host disease (GVHD).…”
Section: Introductionmentioning
confidence: 99%
“…While no studies to date report the effects of myeloablative conditioning on FEV1% for adults with SCD, Saraf et al reported that FEV1% significantly improved 1 year post-HSCT compared to baseline in 12 patients with SCD who underwent non-myeloablative conditioning ( Table 3 ) [ 23 ]. In a more recent study of 122 patients, primarily adults, who received non-myeloablative conditioning with a median follow-up of 4 years [ 24 ], FEV1% predicted remained stable throughout follow-up. Further, the proportion of patients with moderate, moderately severe, and severe defects decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, myeloablative HLA-matched sibling HSCT has emerged as the standard transplant option for eligible children [ 21 ]. HLA-matched sibling HSCT is also highly efficacious in adults using a non-myeloablative approach [ 22 , 23 , 24 ]. As most patients do not have an HLA-matched sibling donor, alternative curative therapy options, including haploidentical HSCT with post-transplant cyclophosphamide, gene therapy, and gene editing, are increasingly available with impressive results [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 20% donor myeloid chimerism has been reported to be sufficient to reverse the acute complications of SCD [ 34 , 35 ]. Recently, investigators reported 122 patients, primarily adults, who underwent non-myeloablative HLA-matched sibling HCT at one of three centers [ 36 ]. At a median follow-up of five years, overall survival was 95% and event-free survival 85%.…”
Section: Introductionmentioning
confidence: 99%